BENCHMARKING UNDERGRADUATE GEOGRAPHY COURSES: A COMPARATIVE STUDY OF THE UNIVERSITY OF ILORIN, NIGERIA, AND UNIVERSITY OF MALAYA, MALAYSIA - Awotayo Gbenga Paul; Norhaslina Hassan; Mariney Mohd Yusoff; Raheem Usman Adebimpe; Orire Ismaila Oloyede, (Malaysian Journal of Tropical Geography (MJTG), 2025)
Undergraduate courses are pivotal in shaping students' futures, guiding their skills and knowledge. Additionally, it forms an integral part of various assessments of educational quality, ranking methodologies, and accreditation prerequisites across educational frameworks. Thus, this study adopts mixed-method approach to benchmark undergraduate geography courses at the University of Ilorin, Nigeria in Africa and University of Malaya, Malaysia, located in Asia continent help identify strengths, weaknesses, and areas for improvement in both departments, offering insights for further development and progress. Analysis of course documents and credit unit distributions reveal differences in core coursework emphasis and program structures. While a strong correlation (r =0.73) exists in course relevance between both universities. The lack of statistical significance (T-Statistics value is 2.62 and P-Value of 0.98) could indicate that other factors are influencing the number of courses offered at both institutions. This might include differences in curriculum design, educational priorities, or regional/geographical influences on the types of courses offered. The study emphasises the significance of benchmarking in geography education for ongoing improvement. It advocates for regular comparisons and comprehensive data analysis to enhance program quality globally.